A bigraphical multi-scale modeling methodology for system of systems. (February 2017) - Gassara, Amal; Bouassida Rodriguez, Ismael; Jmaiel, Mohamed; Drira, Khalil
Highlights: A multi-scale modeling approach for System of Systems design. A formal methodology using Bigraphical reactive systems. A correct by construction approach for describing SoS architectures. An illustration of our methodology with a smart buildings case study. Graphical abstract: Abstract: In this paper, we present a multi-scale modeling methodology for software System of Systems (SoS) using the formal technique of bigraphical reactive system. This methodology provides a correct by design approach ensuring the correctness of the SoS architectures. A first scale is defined by the designer. Then, it is refined by successively adding lower scale details. The transition between scales is implemented following a rule-oriented refinement process. The executed rules respect the system constraints ensuring, in this way, the correctness of the obtained scale architectures. Moreover, we address the dynamic aspect of SoS by providing model-based rules of reconfiguration actions. We illustrate our approach with a Smart Buildings case study.